Comparison of the Stress and Anxiety to Viral Epidemic-9 and SAVE-6 scales among healthcare workers in Peru - Gamonal, Bryan; Quispe-Lizano, Rogelio; Javier-Murillo, Nair; Lapeyre-Rivera, André; Perea-Flórez, Francisco; Velásquez-Rimachi, Víctor; Alva-Diaz, Carlos; Velazco-Gonzales, Gilberth; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2024)
Introduction Peru is a country that has a high incidence of viral outbreaks and epidemics, which is why it is necessary to validate a scale that measures anxiety and stress in professionals who are on the front lines of these events. Therefore, our objective was to validate the Peruvian-Spanish version of the Stress and Anxiety to Viral Epidemics-9 items (SAVE-9) scale and to concurrently compare its validity and internal consistency with the SAVE-6 scale among healthcare workers (HCWs). Materials and methods We conducted a cross-sectional study based on data collected from a self-reported survey in paper-and-pencil format between April and July 2023. A total of 203 HCWs participated in the research. We developed a confirmatory factor analysis (CFA) and item response theory (IRT). We calculated Cronbach’s α coefficient and McDonald’s ω to assess the internal consistency of the scales. Results The results show that SAVE-9 (a two-factor model) and SAVE-6 (a one-factor model) provided an excellent fit in the confirmatory factor analysis. Both scales demonstrated strong internal consistency (Cronbach’s α 0.85 and 0.86, respectively). Significant correlations were found between the SAVE-9 and SAVE-6 scales and Generalized Anxiety Disorder-7 items scale (r = 0.44 and r = 0.38, respectively, p < 0.001) as well as the Patient Health Questionnaire-9 items (r = 0.39 and r = 0.35, respectively, p < 0.001). The optimal cutoff points for SAVE-9 and SAVE-6 were identified for assessing anxiety, aligned with a GAD-7 score ≥5 points. Conclusion The Peruvian-Spanish SAVE-9 and SAVE-6 scales are reliable and valid rating scales to assess the anxiety response of HCWs in response to viral epidemics. Though COVID-19 is diminished, these scales will be useful for other viral epidemics in the future.